AB0714 Monocytes to lymphocytes ratio is correlated with disease activity in behÇet's disease. (12th June 2018) - Huang, Y.; Zheng, S.; Li, T.; Feng, F.; Deng, W.; Huang, Q.; Huang, Z.; Huang, Z.; Pan, X.
Abstract : Background: Behçet's disease (BD) is a complex, inflammatory multisystem disorder. Since the lack of universally recognised pathognomonic laboratory test, the diagnosis relies heavily on clinical findings. Currently, the Monocytes to lymphocytes to ratio (MLR), Neutrophils to Lymphocytes ratio (NLR), Platelets to Lymphocytes ratio (PLR) and Red blood cell Distribution Width(RDW) have been demonstrated as a assessment of disease severity in many rheumatism diseases. Nevertheless, to our knowledge, only a few studies have investigated NLR, PLR, RDW in patients with BD. Objectives: The aim of this study is to determine MLR, NLR, PLR and RDW in BD and to investigate their relationships with disease activity. Methods: A total of 37 patients with BD fulfilling the criteria of the International Study Group for BD and 37 age and gender-matched healthy controls were enrolled in the study retrospectively. MLR, NLR, PLR, RDW, C-reactive protein(CRP) level and Erythrocyte Sedimentation Rate(ESR) level were evaluated. The correlation between the variables were tested with Pearson correlation. Area Under Curve(AUC) value, sensitivity, specificity, and the optimal cut-off values were determined using Receiver Operating characteristic Curves (ROC). According to the optimal cut off value, BD patients were divided into low-value group (<the optimal cut off value) and high value group (≥the optimal cut off value). The patient's clinical characteristics between the two group were compared. Results: The MLR, NLR, PLR and RDW were (0.37±0.24), (2.91±1.95), (155.09±55.08) and (13.83±1.77) in BD group, while (0.18±0.04), (1.45±0.46), (115.66±28.01) and (13.07±1.19) in control group, the difference was significant (P all<0.05). MLR, NLR and PLR were all correlated positively with ESR(r=0.363, P<0.05; r=0.611, P<0.05; r=0.496, P<0.05) and CRP(r=0.713, P<0.05; r=0.785, P<0.05; r=0.394, P<0.05). RDW was not correlated with ESR and CRP. ROC curve results showed that the AUC of MLR, NLR, PLR and RDW for BD were 0.841(CI95%: 0.748–0.935), 0.815(CI95%: 0.712–0.918), 0.720(CI95%: 0.699–0.840), 0.635(CI95%: 0.505–0.765), MLR yielded a highest AUC. In addition, the optimal cut off value of MLR for BD was 0.23, with the specifity of 73.0% and sensitivity of 83.8%. In 37 BD patients, 14 belong to low MLR group, 23 belong to high MLR value group. The comparison results show that high MLR value group have higher CRP level and higher incidence of genital ulceration(P<0.05). Conclusions: MLR was elevated in BD patients as compared to control group, having a close relationship with disease activity. References: [1] Sariyildiz MA, Yazmalar L, Batmaz I, et al. Serum GDF-15 level inBehcet's disease: relationships between disease activity and clinicalparameters. Int J Dermatol2016;55:1289–94 [2] Mercan R, et al. The Association Between Neutrophil/Lymphocyte Ratio and Disease Activity in Rheumatoid Arthritis and Ankylosing Spondylitis. J Clin Lab Anal. 2016; 30(5): 597–601. Acknowledgements: This study was supported by A talent development fund from Guangdong Second Provincial General Hospital (No. 2014001), Medical Scientific Research Foundation of Guangdong Province(No. A2017551). Disclosure of Interest: None declared